2024
DOI: 10.1186/s12906-024-04370-z
|View full text |Cite
|
Sign up to set email alerts
|

Melissa officinalis extract palliates redox imbalance and inflammation associated with hyperthyroidism-induced liver damage by regulating Nrf-2/ Keap-1 gene expression in γ-irradiated rats

Ragaa SM Kawara,
Fatma SM Moawed,
Yakout Elsenosi
et al.

Abstract: Background Melissa officinalis (MO) is a well-known medicinal plant species used in the treatment of several diseases; it is widely used as a vegetable, adding flavour to dishes. This study was designed to evaluate the therapeutic effect of MO Extract against hyperthyroidism induced by Eltroxin and γ-radiation. Methods Hyperthyroidism was induced by injecting rats with Eltroxin (100 µg/kg/ day) for 14 days and exposure to γ-radiation (IR) (5 Gy sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…Based on the aforementioned results, it was found that the sustained oxidative stress was associated with the depletion of the antioxidant defence system and diminished response to excessive ROS leading to suppression of Nrf2 which is a major redox cellular homeostasis transcription factor maintaining cellular antioxidant defence mechanism, 31 detoxifying xenobiotics and pollutants 32 and protecting many organs such as the lungs against impaired redox status and oxidative damage. 33 our results agree with many previous results which showed that lung injury was associated with inhibition of the Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the aforementioned results, it was found that the sustained oxidative stress was associated with the depletion of the antioxidant defence system and diminished response to excessive ROS leading to suppression of Nrf2 which is a major redox cellular homeostasis transcription factor maintaining cellular antioxidant defence mechanism, 31 detoxifying xenobiotics and pollutants 32 and protecting many organs such as the lungs against impaired redox status and oxidative damage. 33 our results agree with many previous results which showed that lung injury was associated with inhibition of the Nrf2.…”
Section: Discussionmentioning
confidence: 99%